2015
DOI: 10.3329/jbsp.v9i2.22796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peanut (Arachis hypogaea L.) on Fasting Blood Glucose and HbA1c in Alloxan Induced Diabetic Male Rats

Abstract: Background: Diabetes mellitus (DM) is a heterogeneous group of metabolic disorders with micro and macrovascular complications which are the major causes of morbidity and mortality in diabetic patients. Peanut due to its anti-oxidant property can reduce blood glucose level and may reduce the risk of diabetes. Objective: To observe the anti-diabetic effects of peanut (Arachis hypogaea L.) in alloxaninduced diabetic male rats. Method: This experimental study was carried out in the Department of Physiology, Sir Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It has been suggested that, some active components of peanut like oleic acid 15 , quercetin (a flavonoid present in peanut) 16 and resveratrol (a poly-phenol phytoalexin present in peanut) 19 stimulate insulin secretion from pancreatic â cells, inhibit the intestinal absorption of glucose 17 , increases insulin sensitivity 19 and ultimately reduces the blood glucose level and lowers the risk of diabetic mellitus 15,34 . Treatment with peanut also improves body weight by increasing insulin secretion and sensitivity, which reduces proteolysis and prevents muscle wasting 13,24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that, some active components of peanut like oleic acid 15 , quercetin (a flavonoid present in peanut) 16 and resveratrol (a poly-phenol phytoalexin present in peanut) 19 stimulate insulin secretion from pancreatic â cells, inhibit the intestinal absorption of glucose 17 , increases insulin sensitivity 19 and ultimately reduces the blood glucose level and lowers the risk of diabetic mellitus 15,34 . Treatment with peanut also improves body weight by increasing insulin secretion and sensitivity, which reduces proteolysis and prevents muscle wasting 13,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Procurement and maintenance of animals 13,22 Forty (40) healthy Wistar Albino male rats, 90 to 120 days old, weighing 225-240 g were used in this study. The animals were purchased from animal house of Department of Pharmacology, Jahangirnagar University, Savar Dhaka.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some researchersobserved hepatoprotective 16 , antidepressant 17 and hypoglyceamic 18 effects of Oyster mushroom in ratsinour country. In addition, mushrooms have antihypertensive 19 ,andlipid lowering effect 20 and it also plays a role in the development and function of the central nervous system 21 .…”
Section: Introductionmentioning
confidence: 99%